Ego Defense Mechanisms in the Main Character Nawai in the Novel Rumah Lebah by Ruwi Meita: Mekanisme Pertahanan Ego pada Tokoh Utama Nawai dalam Novel Rumah Lebah Karya Ruwi Meita - Dina Widya Lestari; U’um Qomariyah (Universitas Negeri Semarang, 2025)
Novels as one of the literary works that represent social and psychological problems become more interesting and diverse to study. The main character